Vicissitudes in the remote presence of the students of the ogram at the Pérez Zeledón Campus, Brunca Regional Headquarters, Universidad Nacional - Madrigal Villanueva, Erick Roberto (2021)
The remote presence (Virtuality) brings a sum of challenges, inconveniences, difficulties, displacements and adaptation processes for students, teachers and the educational system. The objective of the article is to make visible the different vicissitudes that third and fourth year students of the Business Management of Sustainable Tourism program at the Pérez Zeledón Campus, Brunca Regional Headquarters of the Universidad Nacional, have faced over more than a year under the modality of remote presence. Students, mostly from the rural area of the Brunca and Central Pacific Region, who already had an established teaching and learning model, suddenly were exposed to changes due to virtuality, technology, distant communication, without there being any kind of exception at the level of connectivity or access to the internet. This research is qualitative and descriptive, since the appreciations of each of the students are known through the survey instrument and from there comparisons are made with respect to other studies carried out by the university to the entire student population. Some of the results found have been challenges and inconveniences in connectivity, added to a greater workload and even to the acceptance or perception of the type of classes they receive. Finally, this research concludes on how virtuality and in-person modalities have impacted the way of teaching and learning, and revolutionized educational systems, modifying a number of behaviors and methodologies in order to achieve the proposed objective: to obtain a university degree.